Conversion of polypropylene-derived crude pyrolytic oils using hydrothermal autoclave reactor and Ni/aceh natural zeolite as catalysts - Husin, Husni; Mahidin, Mahidin; Marwan, Marwan; Nasution, Fahrizal; Erdiwansyah, Erdiwansyah; Ahmadi, Ahmadi; Muchtar, Syawaliah; Yani, Firda Tirta; Rizalman, Mamat (Elsevier Ltd, 2023)
The accumulation of plastic waste has urged researchers to develop methods of waste conversion into valuable products, which is fuel. This study aimed to synthesize Ni embedded onto Aceh natural zeolite (Ni/Aceh-zeolite) as a cheap catalyst which could be used in the reforming process to improve the quality of oil produced from polypropylene (PP) pyrolysis. Ni/Aceh-zeolite was synthesized from Ni(NO3)2•6H2O and acid-activated natural zeolite through impregnation and calcination. The catalyst was found to have particle sizes ranging from 100 to 200 nm of 20 wt% Ni content. The reforming process using Ni/Aceh natural zeolite with Ni loading of 15 wt% yielded the highest amounts of liquid product (yield = 65%) and gasoline fractions (C5–C12, 96.71%). However, the highest high heating value of 45.467 MJ/kg was found in the liquid product obtained with 20% Ni/Aceh-zeolite. In conclusion, Ni/Aceh-zeolite could be used in the reforming process of PP pyrolysis-derived oil, which could reach a quality similar to that of commercial gasoline.